2019
DOI: 10.1088/1757-899x/546/6/062003
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Flavonoid in Ethanol Extract of Annona squamosa L. Fruit as Xanthine Oxidase Inhibitor

Abstract: The global gout prevalence was increased rapidly in recent decades, especially in some developing countries. One of the most commonly used to treat gout is allopurinol, that act as xanthine oxidase inhibitor. However, consuming allopurinol in the long term can cause some unwanted side effects. On the other hand, many kinds of flavonoid compounds identified in some Indonesian grown plants have bioactivity as xanthine oxidase inhibitor. One of that is sugar apple (Annona squamosa L. fruit). Therefore, the aims o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The concentrations of quercetin-3galactoside (RT = 39.624 min) and quercetin-3-glucoside (RT = 40.485 min) were similar, while a much lower concentration was reported for quercetin-3-rhamnoside. Alvionita and Oktavia [81] reported the presence of quercetin-3-glucoside in the leaf extracts of Annona squamosa L. and indicated that this compound has the properties of an antigout drug due to the strong inhibitory effect on xanthine oxidase. Quercetin was present in both peel and seed portions of Pink's Mammoth.…”
Section: Heat Map and Hierarchical Clustering Analysis Of Phenolic Compoundsmentioning
confidence: 99%
“…The concentrations of quercetin-3galactoside (RT = 39.624 min) and quercetin-3-glucoside (RT = 40.485 min) were similar, while a much lower concentration was reported for quercetin-3-rhamnoside. Alvionita and Oktavia [81] reported the presence of quercetin-3-glucoside in the leaf extracts of Annona squamosa L. and indicated that this compound has the properties of an antigout drug due to the strong inhibitory effect on xanthine oxidase. Quercetin was present in both peel and seed portions of Pink's Mammoth.…”
Section: Heat Map and Hierarchical Clustering Analysis Of Phenolic Compoundsmentioning
confidence: 99%
“…Furthermore, according to Bakar et al (2018), Momordicacharantia, Chrysanthemum indicum, Cinnamomum cassia, Kaempferiagalanga, Artemisia vulgaris, and Morindaelliptica had higher percentages of xanthine oxidase inhibitory activity (>85%) because of their diverse natural bioactive compounds, which include lavonoids, phenolics, tannin, coumarins, luteolin, and apigenin. Besides these plants, Alvionita et al (2019) reported that a lavonoid compound found in Annona squamosal L., has higher binding af inity to the xanthine oxidase than allopurinol which indicated that this plant may be a promising herbal drug for gout treatment. In a review done by Kapoor et al (2017) on over 130 medicinal plants, they concluded that these plants exhibit anti-gout effect by different mechanisms, such as XO inhibition, uricosuric activity, anti-in lammatory activity, and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%